Programma: 11 juni Quicksand, Sun, Stanford Prison Experiment; 15 juni Värttinä; 16 juni Saxual Harassment, Hit the Boom; 17 juni The Muffs, Gas Huffer, Chrome Cranks, Letters to Cleo
Programma: 11 juni Quicksand, Sun, Stanford Prison Experiment; 15 juni Värttinä; 16 juni Saxual Harassment, Hit the Boom; 17 juni The Muffs, Gas Huffer, Chrome Cranks, Letters to Cleo.